Celastrol-loaded liquid crystalline nanoparticles as an anti-inflammatory intervention for the treatment of asthma. Issue 11 (24th July 2021) - Chan, Yinghan; Ng, Sin Wi; Chellappan, Dinesh Kumar; Madheswaran, Thiagarajan; Zeeshan, Farrukh; Kumar, Pradeep; Pillay, Viness; Gupta, Gaurav; Wadhwa, Ridhima; Mehta, Meenu; Wark, Peter; Hsu, Alan; et al.
Abstract: The present study aimed to formulate celastrol into liquid crystalline nanoparticles (LCNPs) through ultrasonication to enhance its therapeutic efficacy in the treatment of asthma. The physiochemical characteristics, in-vitro release studies were determined along with molecular simulations. Celastrol-loaded LCNPs showed the mean particle size of 194.1 ± 9.78 nm and high entrapment efficiency of 99.1 ± 0.02%. TEM revealed cubical-like structure of the nanoparticles and in-vitro release study demonstrated sustained drug release. They also demonstrated significant activity in reducing IL-1β production, when evaluated using immortalized human bronchial epithelial cell lines (BCi-NS1.1), that may help alleviate the symptoms of asthma. Graphical Abstract: UF0001